(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This study systematically investigates the etiopathogenesis, clinical course, and histostructural changes of respiratory distress syndrome (RDS) in neonates born to mothers infected with COVID-19 during pregnancy. Histopathological evaluation revealed alveolar structural disorganization, intra-alveolar fibrinoid exudation, surfactant deficiency, interstitial hemorrhages, and microvascular perfusion defects. These alterations suggest that SARS-CoV-2-mediated placental injury contributes to intrauterine hypoxia and subsequent pulmonary dysfunction. The results provide a foundation for early diagnosis and optimization of neonatal intensive care protocols.